THE RESULTS OF STRENGTH TESTS OF ELECTRIC LOCOMOTIVE DS3 - Blokhin, Ye. P.; Kostrytsia, S. A.; Ostrovierkhov, M. P.; Sultan, O. V.; Datsenko, V. M.; Kryvchykov, O. Ye.; Chumak, V. V. (Science and Transport Progress, 2004)
In paper results of strength tests of electric locomotive DS3 are submitted.